Perspektif Puisi “A Dream Within A Dream” Pada Desain Fashion dan Lifestyle Homespun Spring Summer 2021 - Utomo, Refsi Venny; Herdiana, Wyna; Prianka, Dian (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2020)
Abstract—A Spring/Summer 2021 collection based on WGSN trend forecast for Spring/Summer 2021 called HomeSpun, which inspired from Edgar Allan Poe's poem,